Low-Cost Gas Leak Detection and Surveillance System for Single Family Homes Using Wit.ai, Raspberry Pi and Arduino - Pérez-Palomino, Ximena; Rosas-Paredes, Karina; Esquicha-Tejada, José (International Journal of Interactive Mobile Technologies (iJIM), 2022)
The current situation in the region of Arequipa (Peru) is an increase in crime and insecurity; companies that provide private surveillance services have increased the costs of equipment and services online. We propose is to implement a low-cost gas leakage and surveillance system for single-family houses, implemented with Raspberry Pi3, an Arduino board, SIM 900 module, sensors, actuators, and peripherals. The system alerts by sending a text message when an intruder enters the home or when there is a gas leak; it captures the webcam image that is sent to the homeowner's email. For voice command recognition, Wit.ai and Firebase are used for communication between the system and the mobile application. System functionality and usability tests were carried out, allowing us to know user satisfaction.